1981
DOI: 10.1121/1.387225
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectricity in polyvinylidenefluoride

Abstract: A review of the physical properties of polyvinylidenefluoride (PVDF) with particular emphasis on its piezoelectric activity is given and the applications of this material are discussed. PVDF is a semicrystalline polymer whose crystalline domains appear in four different forms. These forms may be interconverted by the application of heat, electrical fields, and pressure. Thermal poling or corona poling will orient the molecular dipoles in the crystalline parts and thus yield a permanent polarization. This polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(143 citation statements)
references
References 0 publications
4
138
0
1
Order By: Relevance
“…to operate under extreme conditions of high strain and vibration environments. Flexible organic ferroelectric films have been demonstrated 6 and may find applications in specific cases. On the other hand, an integration of oxide-based ferroelectric films with flexible metal substrates offers other opportunities for applications since oxide-based ferroelectric materials exhibit much improved ferroelectric and dielectric properties at high temperature.…”
mentioning
confidence: 99%
“…to operate under extreme conditions of high strain and vibration environments. Flexible organic ferroelectric films have been demonstrated 6 and may find applications in specific cases. On the other hand, an integration of oxide-based ferroelectric films with flexible metal substrates offers other opportunities for applications since oxide-based ferroelectric materials exhibit much improved ferroelectric and dielectric properties at high temperature.…”
mentioning
confidence: 99%
“…Both extrusion and poling of PVDF fibres was carried out in a single continuous process, called as in-line poling on an existing melt extruder line. In other studies reported in the literature the poling process was performed separately outside the extrusion process [15] [16].…”
Section: Production Of Piezoelectric Pvdf Fibrementioning
confidence: 99%
“…Since photoacoustic CT imaging requires custom transducer arrangement, which in turn leads to a dedicated photoacoustic imaging system, greater control over photoacoustic data acquisition can be exercised and time-dependent radiofrequency (containing amplitude, phase, transients, increasing signal-to-noise ratio and improving image quality (14). Typically, photoacoustic signals from biologic absorbers contain frequencies in the range of 1-10 MHz (15), and a broadband US transducer fabricated with polyvinylidene fluoride is more appropriate for photoacoustic imaging compared with lead zirconate titanate transducers conventionally used in clinical US systems (16).…”
Section: Review: Photoacoustic Imaging In Oncologymentioning
confidence: 99%